A New Ruthenium Sensitizer Containing Benzo[1,9]quinolizino(acridin-2-yl)vinyl-2,2′-bipyridine Ligand for Effective Nanocrystalline Dye-Sensitized Solar Cells - Jeum-Jong Kim; Jeonghun Yoon; Eun Jung Kim; Bo Ram Kim; Yong-Jin Yoon; Mangu Kang (International Journal of Photoenergy)
Novel ruthenium bipyridyl sensitizer incorporating conjugated benzo[1,9]quinolizino-(acridin-2-yl)vinyl-2,2′-bipyridine ligand [JJ-12] has been synthesized and demonstrated as efficient sensitizer in dye-sensitized solar cells. A mesoporous titania film stained with JJ-12 exhibits a remarkable incident monochromatic photon-to-current conversion efficiency of 82%. Under standard AM 1.5 sunlight, the solar cell using a liquid-based electrolyte consisting of 0.6 M 1,2-dimethyl-3-propylimidazolium iodide (DMPII), 0.05 M I2, 0.1 M LiI, and 0.5 M tert-butylpyridine in acetonitrile exhibits a short-circuit photocurrent density of 16.47 mA/cm2, an open-circuit voltage of 0.71 V, and a fill factor of 0.71, corresponding to an overall conversion efficiency of 8.34 %.